Researching the registered: challenges and suggestions for researchers studying sex offender populations - Klein, Jennifer L. (Criminal justice studies, 2018)
As interest in registered sex offenders proves to be a popular topic among community members, the media, and legislators alike, researchers must continue to examine the experiences of this offender group. Sex offender registration and community notification laws are diverse across states, creating a difficult and confusing environment for registered sex offenders post-conviction. Often, registered sex offenders report experiences with social stigmatization and physical isolation from their communities as a result of their labeled status. This leads them to be distrustful of outsiders; researchers included. This paper examines the experiences of researchers who have conducted three quantitative and qualitative research projects focused on registered sex offenders and life on the registry. In addition to highlighting the challenges in conducting this type of research, this paper provides a discussion of four specific challenges that may occur when gathering data from community sex offender samples, and several recommendations to overcome these challenges.